CORRELATION OF CUTTING SPEED ON KERF WIDTH AND HAZ DURING CO2 LASER CUTTING OF ALUMINA - Umroh, B.; Rahman, M.N.A.; Solihin, M.; Sultan, A.A.M.; Ebrahim, Z.; Muhamud, R.L.; Ginting, A. (Journal of Advanced Manufacturing Technology (JAMT), 2024)
Alumina is widely used in the automotive, aviation and electronics industries due to its advantages such as high hardness, high melting temperature, and high corrosion resistance. One of the crucial methods to process alumina in those applications is the cutting process. Achieving the right equilibrium between cutting speed and cut quality is crucial, as it directly influences another vital aspect of the cutting process: material removal rate (MRR). The objective of this study is to investigate the correlation between cutting speed and cut quality during CO2 laser machining of alumina. The research involves varying the cutting speed in the range of 500 mm/min to 800 mm/min and measuring the kerf taper angle and heat affected zone (HAZ). The measurements were taken from micrographs obtained using a Stereo Microscope. Regression analysis was performed using Minitab software to assess the strength and significance of the correlation between cutting speed and kerf, taper angle and HAZ. The results indicate a strong and significant correlation between cutting speed and HAZ, with an R2 value of 0.8432 and a P-value of 0.011. Conversely, the study found a weak and insignificant correlation between cutting speed and kerf taper angle, with an R2 value of 0.1540 and a P-value of 0.344.